Impact of ethanol-assisted and non ethanol-assisted mixing methods on the mechanical properties of impregnated polymethylmethacrylate with MgO and Ag nanoparticles - Arf, Awder Nuree; Kareem, Fadil Abdullah; Gul, Sarhang Sarwat (Frontiers in Materials, 2024)
This study aims to elucidate the effect of non ethanol-assisted and ethanol-assisted mixing methods and adding MgO-and Ag-nanoparticles (NPs) into PMMA on flexural strength, impact strength, microhardness (HV) and compressive strength. NPs (1%, 3% and 5% concentrations) were mixed with poly(methyl methacrylate) (PMMA) powder by either using ethanol as a solvent (ethanol-assisted) or without ethanol (non ethanol-assisted). A total of 91 specimens were examined.One-and Two-way ANOVA tests were used to find the effect of mixing methods and concentration of NPs on mechanical properties of PMMA. The results showed an increase of flexural strength for all NPs concentrations (except 1% MgO-NPs) and HV (5% both NPs) in ethanol-assisted groups compared to non ethanol-assisted group (P<0.05). Furthermore, the combined effects of NPs and mixing methods revealed statistically significant increases in flexural strength and HV in ethanolassisted group (except in 1% and 3% MgO-NPs) compared to the control group. Meanwhile, no statistically significant differences were detected in impact strength and compressive strength between ethanol-assisted and non ethanol-assisted groups (P> 0.05). The combined effects of NPs and mixing methods presented a statistically significant increase only in compressive strength of 5% of both NPs in ethanol-assisted group in comparison to the control group. ethanol-assisted mixing of MgO-NPs and Ag-NPs with PMMA showed an increase in the mechanical properties of flexural strength, HV and compressive strength compared to non ethanol-assisted, whereas no improvement in the impact strength property of PMMA was detected. Furthermore, synergetic effects of adding NPs and mixing methods were identified.